Analyzing the Solar Energy Data Using a New Anderson-Darling Test under Indeterminacy. (18th December 2020) - Aslam, Muhammad; Algarni, Ali
Abstract : The generalization of the Anderson-Darling (AD) test under neutrosophic statistics is presented in this paper. We present the designing and operating procedure of neutrosophic Anderson-Darling when the quality of interest follows the neutrosophic normal distribution. The application of the proposed test is given using data from the renewable energy field. From the analysis of the data, it is concluded that the proposed test is effective and information to be applied when the data is recorded from the complex system in the renewable energy field.